RESPON PERTUMBUHAN SEMAI MERANTI MERAH (Shorea leprosula Miq.) TERHADAP PEMBERIAN PUPUK CAIR URIN SAPI DI BAWAH NAUNGAN TEGAKAN KELAPA SAWIT - Elni Segita; M. Mardhiansyah; Viny Volcherina Darlis (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
Shorea leprosula is a Dipterocarpacean tribe that is very adaptive in open areas, both in submerged and dry peatlands. This is one of the triggering factors for cultivating Shorea leprosula plants in Riau, which are predominantly peatlands. Superior plants of Shorea leprosula need to use fertilizers as a medium to improve plant quality. One of them is cow urine waste that can be used at an affordable price and is easily available and has a function as a plant pest control. This study aims to determine the response of the growth of Shorea leprosula to the application of liquid cow urine fertilizer under the shade of oil palm stands. This study used a completely randomized design (CRD), which consisted of 4 (four) treatments, with four replications in order to obtain sixteen experimental units. Each experimental unit consisted of five Shorea leprosula seedlings, with a total number of 80 seedlings. The treatment carried out was administration of cow urine. The results showed that the dose of liquid cow urine fertilizer had an effect on the growth of Shorea leprosula sedlings in the treatment of 20% cow urine liquit fertilizer (K1) by showing the percentage of 100% life yield, and the increase in seed height of 6,86 cm.Keywords : Shorea leprosula, cow urine, peat